The enhancement of infrared light on degradation of trimethoprim - Shuxin Chen; Jing Wang; Qinqin Sun; Jingqing Zhou; Shichong He; Huajun Feng; Pengqian Mu (Catalysis Communications, 2021)
In this study, hydrogenated tungsten oxide(WO3-x) was synthesized. Through experiments, it was found that the material could effectively use infrared light to generate free radicals and effectively remove trimethoprim(TMP). Among them, O2·-and H2O2 are the main types of free radicals. SEM, TEM, XRD, UV–Vis-IR diffuse reflection, and repeatability experiments proved the high efficiency of infrared light utilization and the stability of the material itself. Besides, nine degradation products and two pathways of TMP in the system were first discovered.